Perlindungan Konsumen Atas Peredaran Hand Sanitizer Palsu Yang Tidak Berstandar Kesehatan Di Masa Pendemi Covid-19 - Tresya Klaudia Tutkey; Teng Berlianty; Pieter Radjawane (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Selling health products without a permit that does not meet standards is of course our right as consumers.Purposes of the Research: To know and understand the supervision of the PERMENKES on the circulation of fake Hand Sanitizers that do not have health standards during the covid-19 pandemic. To examine the protection of consumers for the circulation of fake Hand Sanitizers that do not have health standards during the covid-19 pandemic Methods of the Research: The method used is a normative juridical research method using a case approach, a statutory approach and a conceptual approach.Results of the Research: The results obtained from the current research are that consumer protection in fulfilling needs should be obtained by every consumer for health products circulating in the market. However, as time goes by, consumers often get worrisome consequences in terms of health as a result of producers taking shortcuts in order to get as much profit as possible but not matched by the quality improvement provided to consumers. The regulation of the minister of health has a role to maintain the stability of public trust in supervising circulating products, but in reality consumers do not get attention to the circulation of fake hand sanitizers that do not have health standards.